The THE EFFECTIVENESS OF HEALTH EDUCATION TRAINING WITH THE PHANTOM MEDIA DEMONSTRATION METHOD ON KNOWLEDGE AND AWARENESS SKILLS IN SMA NEGERI 3 SAMARINDA - Gading Niken Pramesti; Sri Hazanah (Universitas Widya Gama Mahakam Samarinda, 2024)
In Indonesia, when it comes to female cancers, breast cancer is by far the most lethal. Treatment was delayed because of a lack of education about breast cancer and how to perform a breast self-examination (BSE) for early diagnosis. Real-world targets can learn from and mimic the behaviour displayed in examples through the demonstration technique. Objectives: This study aimed to evaluate the impact of health training using demonstrative techniques and dummy media on female students' knowledge and ability to deal with BSE. Research Metodes: This investigation was quantitative in nature, and a one-group pretest-posttest design was adopted. There were potentially as many as 198 kids at SMA Negeri 3 Samarinda, hence a sample size of 66 was used. Simple random sampling was used. A knowledge and skills questionnaire with a value of 0.05 served as the instrument for this study. Results: A significant effect of health education on female students' knowledge and skills on BSE was found, as indicated by a wilcoxon test p value of 0.05. Conclusion: Health education on BSE delivered using the phantom media demonstration approach has an impact on elevating SMA Negeri 3 students' understanding of the topic. It is anticipated that it can serve as a source of inspiration and education for high school girls. Keywords: Demonstration, SADARI, Knowledge, Skills, Teenager.